2003
DOI: 10.1515/hf.2003.045
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Heat-Treated Wood

Abstract: The aim of this work was to study the wettability and chemical composition of heat-treated wood. Heat treatment was performed at 240°C under inert atmosphere on four European wood species (pine, spruce, beech and poplar). Contact angle measurements before and after treatment indicated a significant increase in wood hydrophobicity. Advancing contact angles of a water drop were in all cases systematically higher for heat-treated than for untreated wood. Chemical modifications of wood after heat treatment were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
125
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(144 citation statements)
references
References 11 publications
(6 reference statements)
18
125
0
1
Order By: Relevance
“…Oliveira et al (2010) described the same wettability behavior found in this study. Pétrissans et al (2005) suggested that wettability decreases due to increase of cellulose crystallinity, whereas Hakkou et al (2005) reported that changes in the conformational arrangement of wood is related to the lignin plasticization or the residual water.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Oliveira et al (2010) described the same wettability behavior found in this study. Pétrissans et al (2005) suggested that wettability decreases due to increase of cellulose crystallinity, whereas Hakkou et al (2005) reported that changes in the conformational arrangement of wood is related to the lignin plasticization or the residual water.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The results are that the mechanical properties of the wood decrease, and dimensional stability and biological resistance of the wood increase (Tjeerdsma et al 1998, Jamsa and Vitainemi 2001, Yildiz 2002, Petrissans et al 2003, Gündüz et al 2008, Can et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The TMP prepared at 170 °C also developed a darker color than the other two TMP types. According to previous studies on thermal treatment of softwood in dry and moist conditions (Sivonen et al 2002;Pétrissans et al 2003;Yin et al 2011), the equilibrium moisture content is expected to be lower for the HT-TMPs. This can be at least partly explained by the degradation of hemicelluloses at elevated temperatures.…”
Section: Preparation Of Tmp Fibersmentioning
confidence: 94%